Analysis of Material Handling Flow Process on Tin Smelting: a Case Study in Indonesia - S, Eko Zunianto; Adhiutama, Akbar (Jurnal Aplikasi Manajemen, 2013)
Indonesia is one of the largest tin producers in the world. Tin industry is growing and flourishing in Indonesia. In Indonesia, the processing of tin ore to tin metal uses reverberatory furnace. Effectiveness on flow of material handling process becomes the determining factor in keeping Work in Process (WIP) mate rial inventory levels and increasing productivity. The purpose of this study is to analyze the flow of material handling processes in order to minimize WIP material inventory and increase productivity. Value Stream Mapping (VSM) is used as a tool to analyze the process flow. Direct field observations and analysis of production data are developed into current VSM. The result reveals that there are some wastes or muda in the process flow. One of the occurring wastes is on the lead time process of the WIP handling which is longer than the cycle time of melting process; therefore, this causes an accumulation of WIP material that results in productivity decreasing of the tin production. Waste elimination can trim the processing time of WIP material handling so that it will be able to reduce the accumulation of WIP material as much as 53% and increase tin production by 5%